Experimental and kinetics study of NO heterogeneous reduction by the blends of pyrolyzed and gasified semi-coke. (15th September 2020) - Yuan, Maobo; Wang, Chang'an; Zhao, Lin; Wang, Pengqian; Wang, Chaowei; Che, Defu
Abstract: The NO reducibility of semi-coke has attracted ever-increasing attention. While little previous work focused on the difference between pyrolyzed and gasified semi-cokes on NO reduction. The co-reduction of pyrolyzed and gasified semi-cokes toward NO deserves specific research to optimize the use of the low-volatile carbon-based fuels. This study focused on NO reduction by the pyrolyzed semi-coke, gasified semi-coke and their respective ash free cokes through a laboratory-scale quartz reactor. Experimental results indicated that the yield of CO2 peaked between 800 °C and 850 °C. The high conversion of CO to CO2 represented strong reaction between NO and semi-coke in NO heterogeneous reduction. The comparison of ash free cokes and their original semi-cokes demonstrated that minerals of semi-coke mainly contributed to the NO reduction below 800 °C. The kinetic analysis revealed that the apparent activation energy of blended semi-cokes increased almost linearly with the decline of pyrolyzed semi-coke fraction. The larger specific surface area benefited the NO diffusion and the adsorption capacity, which lowered the apparent activation energy in the kinetic control zone. Besides, the mixture comprised of 75% pyrolyzed and 25% gasified semi-coke showed a superior NO reduction ratio compared with pyrolyzed semi-coke beyond 750 °C. Highlights: The difference of pyrolyzed and gasified semi-cokes on NO reduction was studied. High conversion of CO to CO2 represented strong reaction between semi-coke and NO. Minerals catalysis of semi-coke mainly contributed to NO reduction below 800 °C. Larger specific surface area lowered the activation energy in kinetic control zone. Partial blends appeared better NO reduction ratio than single semi-coke above 750 °C.